2006
DOI: 10.2355/isijinternational.46.1292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Field on Weld Zone by Spot-welding in Stainless Steel

Abstract: Spot welding is performed through a resistance welding process in which the components to be welded are clamped between two electrodes supplying heat current. It is known that a weld fusion zone and a heat-affected zone (HAZ), which experience high temperature followed by rapid cooling to room temperature, exhibit very different microstructures, compared with those of base materials. The microstructure of the weld fusion zone and HAZ (weld zone) is influenced by many factors such as chemical composition, weldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Ohtsuka et al [59] investigated the transformed structure in a reverse transformation from lath martensite to austenite in a magnetic field and observed an elongated and aligned structure. Watanabe et al [60] spot-welded stainless steel in a magnetic field and observed the structure of the heat-affected zone (HAZ) and found that the area of the HAZ increases with increasing magnetic field. Koyama and Onodera modeled various types of transformation behavior in a magnetic field using the phase-field model and simulated the structural change for Fe-Cr-Co alloy [61] and Ni 2 MnGa [62].…”
Section: Other Transformations In a Magnetic Fieldmentioning
confidence: 99%
“…Ohtsuka et al [59] investigated the transformed structure in a reverse transformation from lath martensite to austenite in a magnetic field and observed an elongated and aligned structure. Watanabe et al [60] spot-welded stainless steel in a magnetic field and observed the structure of the heat-affected zone (HAZ) and found that the area of the HAZ increases with increasing magnetic field. Koyama and Onodera modeled various types of transformation behavior in a magnetic field using the phase-field model and simulated the structural change for Fe-Cr-Co alloy [61] and Ni 2 MnGa [62].…”
Section: Other Transformations In a Magnetic Fieldmentioning
confidence: 99%
“…Popov found that a radially oriented, axisymmetric constant magnetic field could remove the porosity in resistance spot welds of 3.5-mm-thick austenitic nickel-free steel and could improve the impact toughness and fatigue life of the welds [6]. Watanabe et al have proposed that the weld nugget of a spot-welded 301-type stainless steel became larger with an increasing magnetic field applied perpendicular to the welding direction [7]. Shen et al have found that EMS could refine the grain structure, increase the weld nugget diameter, reduce the risk of shrinkage cavities, and improve the mechanical properties of the joint in RSW of advanced high-strength steel DP590 [8] and DP780 [9,10].…”
Section: Introductionmentioning
confidence: 97%
“…To increase the accuracy in numerical simulation, researchers have incorporated the temperature dependent material properties, 15) the effect of magnetic field 16) and presence of surface active elements.…”
Section: Introductionmentioning
confidence: 99%
“…15) With the increasing of magnetic field the weld zone area in unreformed stainless steel is less than that of the weld area in deformed stainless steel. 16) Surface active elements such as oxygen or sulphur present in either shielding gas or in material influence the weld pool shape during GTA welding process. 17) It is quite obvious that the estimation heat source parameters would be intuitively relay on the experimental weld pool shape and size owing to differential influence of peripheral effect such as magnetic effect, surface active element etc.…”
Section: Introductionmentioning
confidence: 99%